Factors Influencing Consumer Adoption of Mobile Payment Systems in the Digital Economy - Nur Sandi Marsuni (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
The rapid growth of the digital economy has accelerated the development of mobile payment systems as an innovative financial technology that enhances transaction efficiency, convenience, and accessibility. Despite the increasing availability of mobile payment services, consumer adoption remains uneven across different demographic and economic contexts. Therefore, understanding the factors that influence consumers’ intentions to adopt mobile payment systems has become an important research issue. This study aims to examine the effects of perceived usefulness, perceived ease of use, trust, perceived security, social influence, mobility, and compatibility on consumers’ behavioral intentions to adopt mobile payment systems. The study employs a quantitative research approach using a survey method. Data were collected from 300 respondents who are familiar with mobile payment services and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that all proposed factors significantly influence behavioral intention to adopt mobile payment systems. Among the examined variables, perceived usefulness emerged as the strongest predictor, followed by trust and compatibility. The results indicate that consumers are more likely to adopt mobile payment technologies when they perceive them as beneficial, secure, trustworthy, easy to use, compatible with their lifestyles, and socially supported. The model explains a substantial proportion of variance in behavioral intention, demonstrating its robustness in explaining consumer adoption behavior. This study contributes to the literature on financial technology adoption and provides practical implications for mobile payment providers, policymakers, and financial institutions seeking to enhance digital payment adoption in the digital economy